The Effect Supply Chain Management Practices and Supply Chain Integration on The Performance of Malang City SMEs - Yoga, Tirta; Djoko Koestiono; Agustina Shinta (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2022)
This study aimed to know whether there is a significant effect of supply chain management practices and supply chain integration on Micro, Small, and Medium Enterprises (MSMEs) performance in the food and beverage agroindustry of Malang City. This research used a quantitative approach conducted in Malang City in 2021. The data were collected through a questionnaire from 100 MSMEs in the food and beverage agroindustry of Malang City. The hypothesis in this research was tested using the analysis method of Structural Equation Modeling (SEM) by using Partial Least Square (PLS). The study was able to prove the existence of a significant effect of Supply Chain Management and Supply Chain integration on the performance of MSMEs agroindustry. MSMEs should continue to improve and implement Supply Chain Management practices because these factors are proven to affect operational performance.